Pengembangan Model Manajemen Pendidikan Islam Berbasis Teknologi untuk Meningkatkan Akses dan Kualitas Pendidikan - Haryati Haryati; Andri Andri; Maulina Nabila (Syntax Corporation Indonesia, 2024)
This research aims to create a management model that integrates technology effectively in the management and learning process in Islamic educational institutions, so that it can expand the reach of education to more students, including in remote areas, as well as improve the quality of education through the use of technology that supports interaction, collaboration, and learning innovation. A qualitative descriptive method was used in this study, the data collection technique used was a literature study, while the data obtained was analyzed by Miles & Huberman interactive analysis with a three-stage process, namely reduction and presentation of data and drawing conclusions. The results of the analysis found that the development of a technology-based Islamic education management model is important to improve access and quality of education in the digital era. Various technologies present in the development of the digital era help in interactive learning, accessibility, and student performance evaluation, as well as help develop digital skills and character according to Islamic values. With responsive management, Islamic educational institutions can adapt to changes while maintaining the holistic essence of education.